Implementation of Social Security Protection for Workers at the Village Level (Research Study at Langsa City-Aceh) - Bustami Bustami; Rini Fitriani; Liza Agnesta Krisna (International Journal of Applied Business and International Management, 2018)
This research aims to analyze the implementation of social security protection for works at the village level through Social Security Administrator (BPJS) at Langsa city, Aceh. The type of this research is juridical Empirical, approach methodology that used in this research is sociological juridical which get the truth in empirical way by reviewing directly to the people about the implementation of social security protection for workers at the village level. In fact, the implementation of social security protection for workers at the village level has not ran optimally, even though the dues for the social security protection is not from the workers’ salary, but funded by the government, there are 2 (two) obstacles that faced which is internally each village’s headman wisdom, and the workers’ incomprehension to the rights of the social security protection for workers they have, meanwhile externally is lack of socialization from the Social Security Administrator (BPJS) so that there is information misunderstanding that received by the village’s headman, and the election for the new village’s headman is still on process. The effort to increase the socialization and give the understanding in detail to the village’s headman about the purpose and the use of social security protection for workers.